Lasers and light, peels and abrasions applications and treatments - Truswell, William, 1946- (Thieme, 2016)
Lasers and Light, Peels and Abrasions is a comprehensive clinical reference on all invasive and non-invasive treatments for aging, diseased, and congenitally deformed skin. Every treatment modality that's used for skin rejuvenation, scars, complications, vascular abnormalities, and ethnic skin type variations, and more, is explained in detail.